The Metalexicographical Contribution of Pedro A. Fuertes-Olivera and Ascensión Arribas-Baño's Pedagogical Specialised Lexicography: A Critical Review - Nkomo, Dion (Lexikos, 2009)
Abstract: This article attempts to give a critical review of Pedro A. Fuertes-Olivera and Ascensión Arri-bas-Baño's Pedagogical Specialised Lexicography. It evaluates the book in view of the available meta-lexicographical literature as well as current trends in practical LSP lexicography in the wake of rapid tech-nological and information developments. The article appreciates both the methodological and theoretical frameworks within which the book identifies, investigates and addresses lexicographical problems. The ap-proaches make the book an important academic contribution with critical insights for metalexicographers, especially in the area of dictionary criticism. The theoretical insights provided in the book further possess the potential to accomplish exactly what metalexicography ought to accomplish, i.e. to facilitate the production of user-friendly dictionaries which meet both the reference needs and reference skills of the targeted users. A few concerns are, however, raised mainly regarding the technical aspects of the book. While these may have a negative impact on the reader, they are not severe enough to discredit the rigour with which the book was conceived.Keywords: METALEXICOGRAPHY, PEDAGOGICAL SPECIALISED LEXICOGRAPHY, MONOLINGUAL LSP DICTIONARY, BILINGUAL LSP DICTIONARY, MEANING REPRE-SENTATION, DICTIONARY STRUCTURES, DEFINITIONS, EQUIVALENCE, EXAMPLES, DICTIONARY CRITICISMOpsomming: Die metaleksikografiese bydrae van Pedro A. Fuertes-Olivera en Ascensión Arribas-Baño se Pedagogical Specialised Lexicography: 'n Kri-tiese beskouing. Hierdie artikel probeer om 'n kritiese beskouing van Pedro A. Fuertes-Olive-ra en Ascensión Arribas-Baño se Pedagogical Specialised Lexicography te gee. Dit beoordeel die boek met betrekking tot die beskikbare leksikografiese literatuur, sowel as huidige neigings in praktiese TSD leksikografie in opvolging van die vinnige tegnologiese en inligtingsontwikkelinge. Die artikel het 'n waardering vir sowel die metodologiese as teoretiese raamwerk waarbinne die boek die lek-sikografiese probleme bepaal, ondersoek en aanpak. Die benaderings maak die boek 'n belangrike akademiese bydrae met kritiese insigte vir metaleksikograwe, veral op die gebied van woorde-boekkritiek. Die teoretiese insigte wat in die boek verskaf word, besit verder die moontlikheid om dit te bewerkstellig wat metaleksikografie behoort te bewerkstellig, d.i. om die voortbrenging van gebruikersvriendelike woordeboeke te vergemaklik wat sowel die naslaanbehoeftes as die naslaan-vaardighede van die teikengebruikers bevredig. 'n Paar bedenkinge word egter geopper hoofsaak-lik betreffende die tegniese aspekte van die boek. Alhoewel hulle 'n negatiewe uitwerking op die leser kan hê, is hulle nie ernstig genoeg om die noukeurigheid aan te tas waarmee die boek beplan is nie.Sleutelwoorde: METALEKSIKOGRAFIE, OPVOEDKUNDIGE GESPESIALISEERDE LEK-SIKOGRAFIE, EENTALIGE TSD-WOORDEBOEK, TWEETALIGE TSD-WOORDEBOEK, BETE-KENISAANBIEDING, WOORDEBOEKSTRUKTURE, DEFINISIES, EKWIVALENSIE, VOOR-BEELDE, WOORDEBOEKKRITIEK